NEUROEDUSINGULARITY: THE ENCOUNTER BETWEEN HUMAN MINDS AND ARTIFICIAL MINDS (Editora Impacto Científico, 2025)
NeuroEduSingularity (NES) emerges as a conceptual framework that integrates neuroscience, artificial intelligence, and exponential learning, proposing a new paradigm for understanding the relationship between the human mind and emerging technologies. This article analyzes the foundations of Technological Singularity and its transition to the cognitive-educational field, highlighting how phenomena such as informational acceleration, technological convergence, and advanced AI models cause disruptions in traditional teaching models. From an interdisciplinary approach, the impact of technological time leaps on neural plasticity, skills development, and the redefinition of the educator's role in hyperconnected environments is discussed. It is argued that NES represents not only an evolutionary stage of digital technologies but a cognitive-temporal collapse that redefines how we learn, perceive the world, and relate to non-biological intelligence. The analysis points out that, in the face of the emergence of self-adaptive systems and emergent AI behaviors, it becomes urgent to reflect on ethics, autonomy, techno-surveillance, and the preservation of human identity. Finally, it is proposed that the education of the future depends on hybrid models that reconcile human depth, co-authoring artificial intelligence, and immersive experiences—inaugurating an ecosystem where learning becomes continuous, adaptive, and integrated with technological evolution itself.DOI: https://doi.org/10.56238/edimpacto2025.090-062